PENGARUH MARKETING MIX, INOVASI PRODUK, DAN MEREK TERHADAP KEPUASAN KONSUMEN PRODUK AGRIBISNIS: STUDI KASUS PADA USAHA AIR MINUM DALAM KEMASAN (AMDK) LOKAL DI KOTA AMBON - Susana Manuhutu, Louisa (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The agribusiness sector faces increasingly competitive challenges, especially in local food processing businesses. This study aims to analyze the effect of marketing mix, product innovation, and brand on consumer satisfaction for the Ayudes brand bottled water (AMDK), as a representation of local agribusiness processed products in Ambon City. The research uses a quantitative method with a descriptive-correlational approach. The sample consisted of 52 consumers selected through purposive sampling. Data were collected via Likert-scale questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 25. The results show that: (1) marketing mix has a positive and significant effect on consumer satisfaction (t = 2.190; sig. = 0.033); (2) product innovation has a positive and significant effect (t = 2.146; sig. = 0.037); (3) brand has a positive and significant effect (t = 3.090; sig. = 0.003); and (4) all three variables simultaneously have a significant effect (F = 41.522; sig. = 0.000). The coefficient of determination (R²) of 70.4% indicates that consumer satisfaction variation is largely explained by these three variables. These findings imply the importance of integrated marketing strategy, continuous innovation, and brand management in local agribusiness enterprises.